Robotic Surgery in Gynecology - Bouquet de Joliniere, Jean; Librino, Armando; Dubuisson, Jean-Bernard; Khomsi, Fathi; Ben Ali, Nordine; Fadhlaoui, Anis; Ayoubi, J. M.; Feki, Anis (Frontiers in Surgery, 2016)
Abstract Minimally invasive surgery (MIS) can be considered as the greatest surgical innovation over the past thirty years. It revolutionized surgical practice with well-proven advantages over traditional open surgery: reduced surgical trauma and incision-related complications, such as surgical-site infections, postoperative pain and hernia, reduced hospital stay, and improved cosmetic outcome. Nonetheless, proficiency in MIS can be technically challenging as conventional laparoscopy is associated with several limitations as the two-dimensional (2D) monitor reduction in-depth perception, camera instability, limited range of motion and steep learning curves. The surgeon has a low force feedback which allows simple gestures, respect for tissues and more effective treatment of complications. Since 1980s several computer sciences and robotics projects have been set up to overcome the difficulties encountered with conventional laparoscopy, to augment the surgeon's skills, achieve accuracy and high precision during complex surgery and facilitate widespread of MIS. Surgical instruments are guided by haptic interfaces that replicate and filter hand movements. Robotically assisted technology offers advantages that include improved three- dimensional stereoscopic vision, wristed instruments that improve dexterity, and tremor canceling software that improves surgical precision.